Critical stress and thermal activation of crystal plasticity in polyethylene: Influence of crystal microstructure and chain topology. (2nd June 2017) - Xiong, Bijin; Lame, Olivier; Chenal, Jean-Marc; Men, Yongfeng; Seguela, Roland; Vigier, Gerard
Abstract: The influence of microstructure and temperature on the initiation of yield stress and strain of high-density polyethylene are examined using a set of linear and branched polyethylenes. The polymers were crystallized in different ways in order to get samples covering the range of crystallinity 0.5 ≤ X c  ≤ 0.8 and crystallite thickness 8 nm ≤  L c  ≤ 29 nm. In contrast to the conventional macroscopic yield strain and stress, the initiation strain ε yi and stress σ yi were estimated from the macroscopic stress-strain curves at the onset of local plasticity as judged from in situ WAXS experiments upon tensile deformation. Phenomenological linear relation was observed between σ yi crystallinity at each draw temperature T d . The dislocation model was applied to check the correlation between σ yi and crystal thickness. In order to also account for the chain topology, namely the concentration of stress transmitters ST, a modified Eyring's approach was proposed. This modelling provides a good prediction the σ yi dependence on L c and ST in the context of thermally activated rate processes. Finally, anelastic stress gauge, σ c cr, was determined from local strain measurements in crystals at the same local strain as for σ yi . This critical elastic stress at initiation of crystal plasticity displayed a good correlation with σ yi at high crystallinity. However, σ c cr was found to deviate from σ yi with increasing T d particularly at low X c values. This finding was attributed to the activation of the crystalline mechanical relation that involves a significant drop of σ yi with increasing T d in the crystalline lamellae under shear yielding whereas it does not affect the theoretical σ c cr elastic stress. Graphical abstract: Highlights: Accurate WAXS measurement of crystal strain in the low strain domain. Determination of strain onset for local crystal yielding. Computing critical crystal stress at onset of crystal yielding. Evidence of variable stress transfer between lamellae depending on crystallinity.